Utilization of PjBL-STEM Based Interactive e-modules to Improve Visual Literacy: Teacher and Student Perspectives - Dini Andriani; Marina Setyarini; Dewi Lengkana; Kartini Herlina (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to describe the use of interactive e-modules based on PjBL-STEM activities to train students' visual literacy.  This research uses mixed methods with sequential explanatory design to obtain quantitative and qualitative data.  Quantitative data was obtained by administering questionnaires to 39 science teachers in Lampung province and 149 junior high school students and qualitative data was obtained from interviews with teachers. The research results show as many as 41.70% of teacher respondents were new to using e-module teaching materials.  The e-module they use is not yet interactive and the activities in the e-module do not invite students to carry out projects.  The results of the teacher questionnaire were only 15.3% of teacher respondents using the PjBL learning model.  As many as 74.5% of teacher respondents stated that the e-modules used had not been used to train students' visual literacy.  The results of the questionnaire and interviews of teachers responded positively to the existence of teaching materials that can train students' visual literacy.